Sistem Pendukung Keputusan Pemilihan Smartphone Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Website - Aldi Fernando Liusman; Rudy Arijanto (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
The rapid development of technology creates a wide variety of tools that support their lives. Smartphone products are one of the technological tools that have a major influence on human life. Smartphones are technological tools used in communicating that have advanced features such as storing photos, sending pictures, downloading applications, and communicating with other smartphone users. This tool has an affordable price for the community and is practical to carry because of its small size. The rapid development of smartphones has caused problems for the community. Smartphones have different specifications such as processor type, screen size, battery capacity, camera resolution, storage, RAM, and various operating systems, resulting in people having problems choosing a smartphone. The solution that can solve this problem is to implement a Decision Support System with the Simple Additive Weighting (SAW) Method. This method can provide the best alternative to various existing smartphones based on the criteria present in the system. The system is built on a website basis, so users can access the system as long as the user has internet. The results of this study are expected to provide convenience for users in determining which smartphone to use by adjusting their wants, needs, and budget.